Evaluation of trace elements in Malay women with type 2 diabetes mellitus - Mohammed Nashiry,; Ismarulyusda Ishak,; Jamaludin Mohamed,; Siti Balkis Budin,; Mohd Fairulnizal M.N.,; Sazlina Kamaralzaman,; Al-Mekhlafi, Hesham M. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Trace elements are essential for human health. This study determines the level of chromium (Cr), zinc (Zn), selenium (Se), copper (Cu), ferrum (Fe) and manganese (Mn) in the hair and nails of married Malay women with type 2 diabetes mellitus from Hulu Langat, Selangor, Malaysia. The trace elements were analysed using inductively coupled plasma mass spectrometry (ICP-MS) after an acid digestion treatment. The levels of all trace elements measured were higher in the hair samples than in nails except for Se. Mean levels of Zn and Se were significantly higher in the hair of non-working women (84.91 ± 10.32 μg/g and 0.42 ± 0.15 μg/g, respectively) compared to working women (64.98 ± 11.10 μg/g and 0.30 ± 0.18 μg/g). Copper levels in hair were significantly higher among women with good and satisfactory diabetes control (20.41 ± 4.20 μg/g) compared to the poor diabetes control group (15.67 ± 4.31 μg/g). However, a contradictory result was obtained from the nails of women with good and satisfactory diabetes control with a Cu level of 3.35 ± 0.46 μg/g and 4.69 ± 0.33 μg/g for the poor diabetes control group. In hair samples, significant positive correlations were obtained with Cr-Cu (r = 0.55), Zn-Mn (r = 0.46) and Se-Mn (r = 0.38). In nails, significant positive correlations were also obtained between Cr-Zn (r = 0.31), Zn-Fe (r = 0.30) and Fe-Mn (r = 0.47). In conclusion, age, educational status, number of children and duration of diabetes did not influence trace elements levels.